2017
DOI: 10.1631/jzus.b1600223
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, characterization, and promoter analysis of the isochorismate synthase (AaICS1) gene from Artemisia annua

Abstract: Abstract:Isochorismate synthase (ICS) is a crucial enzyme in the salicylic acid (SA) synthesis pathway. The full-length complementary DNA (cDNA) sequence of the ICS gene was isolated from Artemisia annua L. The gene, named AaICS1, contained a 1710-bp open reading frame, which encoded a protein with 570 amino acids. Bioinformatics and comparative study revealed that the polypeptide protein of AaICS1 had high homology with ICSs from other plant species. Southern blot analysis suggested that AaICS1 might be a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The RAV subfamily is involved in the signal transduction of ethylene and other plant hormones ( Alonso et al, 2003 ), Brassinosteroid ( Hu et al, 2004 ), and also participated in the water stress tolerance of DREB subfamily members. The DREB genes with a conservative binding sequence CCGAC commonly bind to the main LTR and/or MBS (core sequences: CCGAAA and C/TAACTG) cis -acting elements upstream of the gene and plays a crucial role in resisting biological stress (including cold and drought) effect ( Hogan et al, 2003 ; Wang et al, 2017 ). Additionally, the transcription factors from the ERF subfamily binds with GCC-boxes which are entangled in different pathways of hormone signaling, like ethylene, 2-hydroxybenzoic acid, and jasmonic acid pathways ( Fujimoto et al, 2000 ; Oñate-Sánchez and Singh, 2002 ; Mantiri et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…The RAV subfamily is involved in the signal transduction of ethylene and other plant hormones ( Alonso et al, 2003 ), Brassinosteroid ( Hu et al, 2004 ), and also participated in the water stress tolerance of DREB subfamily members. The DREB genes with a conservative binding sequence CCGAC commonly bind to the main LTR and/or MBS (core sequences: CCGAAA and C/TAACTG) cis -acting elements upstream of the gene and plays a crucial role in resisting biological stress (including cold and drought) effect ( Hogan et al, 2003 ; Wang et al, 2017 ). Additionally, the transcription factors from the ERF subfamily binds with GCC-boxes which are entangled in different pathways of hormone signaling, like ethylene, 2-hydroxybenzoic acid, and jasmonic acid pathways ( Fujimoto et al, 2000 ; Oñate-Sánchez and Singh, 2002 ; Mantiri et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study confirmed that many important cis -regulatory elements already existed in the promoter regions of stress response genes in MYBs, WRKYs, and MADS-boxes [ 35 , 40 , 46 ]. Furthermore, many of these elements, such as ABREs and DREs, have been reported to widely participate in abiotic stress responses in Artemisia annua , Arabidopsis and wheat [ 47 , 48 , 49 ]. However, no study has investigated these key regulatory elements in alfalfa.…”
Section: Discussionmentioning
confidence: 99%